`(x^2 +2x-8)/(x-1) X (x^3+8)/(4(x-2)-x^2 (x-2))`

`==> ((x+4)(x-2))/(x-1) X ((x+2)(x^2-2x+4))/((x-2)(4-x^2))`

`==> ((x+4)(x-2))/(x-1) X ((x+2)(x^2-2x+4))/((x-2)(2-x)(2+x))`

Reduce similar terms:

==> `(x+4)/(x-1) X (x^2-2x+4)/(2-x)`

``

`==> ((x+4)(x^2-2x+4))/((x-1)(2-x))`

``

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now